2016
DOI: 10.2147/ott.s100407
|View full text |Cite
|
Sign up to set email alerts
|

Toward a noncytotoxic glioblastoma therapy: blocking MCP-1 with the MTZ Regimen

Abstract: To improve the prognosis of glioblastoma, we developed an adjuvant treatment directed to a neglected aspect of glioblastoma growth, the contribution of nonmalignant monocyte lineage cells (MLCs) (monocyte, macrophage, microglia, dendritic cells) that infiltrated a main tumor mass. These nonmalignant cells contribute to glioblastoma growth and tumor homeostasis. MLCs comprise of approximately 10%–30% of glioblastoma by volume. After integration into the tumor mass, these become polarized toward an M2 immunosupp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 126 publications
0
18
0
Order By: Relevance
“…The drugs were instead effective in combination with temozolomide, significantly increasing mice survival [27] . Interestingly, it has been shown that the production of MCP-1 by glioma cells can be efficiently reduced by non-cytotoxic drugs, including the antibiotic minocycline, the angiotensin II receptor inhibitor telmisartan and the bisphosphonate zolendronic acid [40] . These drugs have a good BBB penetration and will be tested in combination as an ancillary therapy to improve the outcome of currently approved cytotoxic regimens.…”
Section: Drugs That Interfere With Gams' Recruitment At the Tumor Sitementioning
confidence: 99%
“…The drugs were instead effective in combination with temozolomide, significantly increasing mice survival [27] . Interestingly, it has been shown that the production of MCP-1 by glioma cells can be efficiently reduced by non-cytotoxic drugs, including the antibiotic minocycline, the angiotensin II receptor inhibitor telmisartan and the bisphosphonate zolendronic acid [40] . These drugs have a good BBB penetration and will be tested in combination as an ancillary therapy to improve the outcome of currently approved cytotoxic regimens.…”
Section: Drugs That Interfere With Gams' Recruitment At the Tumor Sitementioning
confidence: 99%
“…40,44,45 These studies have led to the proposal of MCP-1 blockade as a treatment for GBM. 46,47 A detailed examination of human gliomas demonstrated that MCP-3, not MCP-1 correlates with myeloid cell accumulation in glioblastoma, 48 calling into question the utility of MCP-1 inhibition in preventing TAM infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in hepatocellular carcinoma TGF-beta synthesized and released by tumor infiltrating monocytes, drives the proper carcinoma cells’ EMT [ 119 ]. A parallel relationship between monocyte lineage cells and malignant phenotype has been described in GB as well [ 120 ].…”
Section: The Eis Regimen: Emt Triggers Maintenance Factors and 6 Cumentioning
confidence: 95%